Perceptions in the use of technology for payments: a study of customer behavior in food and beverage sector - Furtado, Nilton Gomes; Canto, Rodrigo Souza; Oliveira, Sergio Luis Ignacio de; Moretti, Sergio Luiz do Amaral (Ágora : revista de divulgação científica, 2017)
Surveys indicates that companies in the food and beverage sector in Brazil, are cautious in the adoption of payment technology with the use of mobile devices. Aiming to investigate the relationship between consumer behaviour on new techonology’s use and adoption in this sector, this paper explore the costumers expectations and perceptions on the mobile payment technology applied on the food and beverage industry. The method involved as inquiry with 80 interviewees, that suggested changes and quick addoptance among comercial establishments on new techonology devices/resources. All interviewees were aware of costumer driven payment Technologies such as mobile apps, tablets, remote cashiers and payments devices and the totality expect to install and use those technology devices on their restaurants in the next couple years. Potencial benefits of eletronic self payment for clientes includes, a faster process, less team waiting time (maitre, waiter or cashier), higher safety and costumer satisfaction, reduction on labor costs, higher incomen due to higher table rotation e access to better costumer data. Ironically, safety is considered a potential barrier. Other barriers include infra-estructure issues, devices costs, POS and devices payments intregration costs, the impact of lower costumer/team contact and the fact that the the technology already availble in the industry is fragmented and in embrionary phase.